2021
DOI: 10.3390/ijerph18168281
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of U.S. Housing Type and Residential Living Situations on Mental Health during COVID-19

Abstract: Residential environments could be associated with the mental health of residents, in general, and during the COVID-19 pandemic. However, limited studies have investigated the relationship between these two. This study used data from the Household Pulse Survey, collected between 23 April 2020 and 23 November 2020 to explore the relationship between mental health status as perceived by the residents and housing tenure (own or rent), building type, and the number of household members, while accounting for sociode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…During the lockdowns, social interaction and support provided by people who shared housing reduced their perception of loneliness and isolation (compared to people who live alone), as reflected in the results of this study. Our results are consistent with other forms of shared housing, like cohousing communities (Izuhara et al, 2022 ), housing cooperatives (Guity-Zapata et al, 2023 ), multifamily housing (Ghimire et al, 2021 ), that indicate that living with more people during the pandemic contributed to the reduction of mental health issues. The results of this study indicate that the number of adults at home during pandemic-like crisis events can be both positive for relationship building and negative due to space constraints and disruptions.…”
Section: Discussion and Limitationssupporting
confidence: 89%
“…During the lockdowns, social interaction and support provided by people who shared housing reduced their perception of loneliness and isolation (compared to people who live alone), as reflected in the results of this study. Our results are consistent with other forms of shared housing, like cohousing communities (Izuhara et al, 2022 ), housing cooperatives (Guity-Zapata et al, 2023 ), multifamily housing (Ghimire et al, 2021 ), that indicate that living with more people during the pandemic contributed to the reduction of mental health issues. The results of this study indicate that the number of adults at home during pandemic-like crisis events can be both positive for relationship building and negative due to space constraints and disruptions.…”
Section: Discussion and Limitationssupporting
confidence: 89%
“…Home ownership and household size are two factors that reflect housing conditions. Several studies have suggested that the impact of housing condition on mental health has been significant during the pandemic ( Amerio et al., 2020 ; Ghimire et al., 2021 ). Finally, we asked the respondents to report whether their neighborhoods were currently under lockdown, whether they have ever been quarantined, and whether there were confirmed cases in their neighborhood.…”
Section: Methodsmentioning
confidence: 99%
“…Studies published in recent literature have started investigating, in a systematic way, the overall quality of built environment [ 29 , 30 ] and living spaces, revealing that the absence of accessible outdoor space from the house (e.g., garden, terrace) contributed to concerning levels of psychological and behavioral symptomatology [ 31 ], confirming that housing environments could be associated with the mental health and wellbeing of residents [ 32 , 33 , 34 , 35 , 36 ]. While mental illnesses can be investigated through structured and validated scales, housing quality is mainly assessed in terms of occupants’ perception, due to the complexity of surveying a high number of different apartments and the low psychometric reliability of existing tools [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%